(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2025)
In this article, the sociocultural situation of the Polish readers of a popular crime series by Karin Wahlberg is contrasted with the situation of readers in Western countries. It is argued that a presentation of generic masculine words in the former setting as merely reflexive of gender inequalities that exist may prevent the Polish readers from homing in on what seems to be a message contained in the original, i.e. the capability of language to construe inequality and not just reflect it.